Pengaruh Budaya Organisasi dan Pemanfaatan Teknologi Tehadap Kinerja Karyawan Melalui Kepuasan Kerja Karyawan Sebagai Variabel Intervening Pada PT. Semen Padang - Rana Pertiwi; Robby Dharma; Omia Crefioza (CV. ITTC INDONESIA, 2026)
This study aims to identify and analyze the influence of organizational culture and technology utilization on employee performance through employee job satisfaction as an intervening variable at PT Semen Padang. This research uses the Structural Equation Modeling (SEM) approach with SmartPLS 3.0 as the analytical tool. The population and sample of this study are the employees of PT Semen Padang. The results show that there is a positive and insignificant effect of organizational culture on employee job satisfaction, a positive and significant effect of technology utilization on employee job satisfaction, a positive and significant effect of organizational culture on employee performance, a positive and significant effect of technology utilization on employee performance, a positive and insignificant effect of employee job satisfaction on employee performance. Furthermore, employee job satisfaction is not able to mediate the effect of organizational culture on employee performance and is not able to mediate the effect of technology utilization on employee performance